Impact of "Yoga Based Lifestyle Interventions" and its Implications on Health and Disease - Rathore, Mrithunjay; Verma, Meghnath; Abraham, Jessy; Dada, Rima; Kumar, Manoj (International Research Journal of Ayurveda & Yoga, 2023)
Yoga and meditation address mind and body, affecting many molecular processes like metabolism, epigenetic, oxidative processes, and subjective well-being. In this review, we have compiled the results of various clinical trials that have looked into the effect of yoga-based intervention programs on gene expression changes in peripheral blood mononuclear cells (PBMCs). Most yoga-based interventions aided in the maintenance of genomic stability through maintenance of telomere length and showed improvement in innate immunity. However, there is a lack of randomization and variability in the duration of intervention programs across studies. So, future trials should focus more on rigorous methods and reporting adequate sample size and randomization. Aim: To explores the effect of yoga on physical health through observable molecular changes in the form of differential gene expression and the molecular changes underpinning psycho physiological benefits.Materials and Methods: we reviewed different types of Mind body interventions (MBIs) of various observable molecular changes in the form of differential gene expression. Result and discussion: This review adds to the ever-growing literature on the effects of Yoga/MBIs on health and disease, specifically the changes in the regulation of gene expression levels. Conclusion: our review article suggests that a comprehensive yoga program induces significant gene expression changes. By adopting a yoga and meditation-based lifestyle, we surely can slow down the pace of our biology or chronological age